A novel expression vector for the secretion of abaecin in Bacillus subtilis - Li,Li (2017)
ABSTRACT This study aimed to describe a Bacillus subtilis expression system based on genetically modified B. subtilis. Abaecin, an antimicrobial peptide obtained from Apis mellifera, can enhance the effect of pore-forming peptides from other species on the inhibition of bacterial growth. For the exogenous expression, the abaecin gene was fused with a tobacco etch virus protease cleavage site, a promoter Pglv, and a mature beta-glucanase signal peptide. Also, a B. subtilis expression system was constructed. The recombinant abaecin gene was expressed and purified as a recombinant protein in the culture supernatant. The purified abaecin did not inhibit the growth of Escherichia coli strain K88. Cecropin A and hymenoptaecin exhibited potent bactericidal activities at concentrations of 1 and 1.5 µM. Combinatorial assays revealed that cecropin A and hymenoptaecin had sublethal concentrations of 0.3 and 0.5 µM. This potentiating functional interaction represents a promising therapeutic strategy. It provides an opportunity to address the rising threat of multidrug-resistant pathogens that are recalcitrant to conventional antibiotics.